On the Formation of Solid Solutions at Thermobaric Sintering of PcBN Composites of cBN–MeN–Al and cBN–MeC–Al Systems - N.M. Bilyavyna, V.Z. Turkevych, D.A. Stratiichuk, A.M. Kuryliuk, and O.I. Nakonechna (Успехи физики металлов)
Using the x-ray diffraction method, we study in detail a series of polycrystalline cubic boron nitride (PcBN) composites of the cBN–{TiN, ZrN, HfN, VN, NbN}–Al and cBN–{TiC, ZrC, HfC, VC, NbC, TaC}–Al systems (with a charge composition of 60:35:5 vol.%) sintered at high pressures and high temperatures (HPHT): 7.7 GPa, 1600–2450 °C. As shown, the crystal structure of each nitride MeN or carbide MeC (Me = Ti, Zr, Hf, V, Nb, Ta) existing in these composites belongs to a modified NaCl-type structure with the additional position for nitrogen atoms that results in the accumulation of N-atoms’ excess in the near-surface layers of composites. Al atoms of the charge are embedded into the MeC crystal lattice at certain sintering temperatures forming substitutional solid solutions based on a relevant metal Me. The existence ranges of temperature and composition of MeN1+δ, MeCNδ, and Me1−xAlxCNδ solid solutions formed at HPHT sintering are determined. As shown, the crystal-structure features revealed in these solid solutions are in a good agreement with theoretical assumptions on the solid-phase interaction of the charge components at sintering. Thus, the accumulation of nitrogen in MeN and MeC phases is described within the atomistic diffusion model. Using the data on the excess of N in nitrides as the reference values, the main parameters of nitrogen diffusion (activation energy and rate constant) within the cBN–{TiN, HfN, VN, NbN}–Al composites are determined. The formation of Al solid solutions at certain modes of HPHT sintering is explained by the mechanism of interaction of liquid aluminium with MeC, which is preceded by the active formation of vacancies in the metal sublattice of these carbides. Methodologically, the x-ray diffraction study data are applied for the first time to determine the main parameters of the N-atoms’ migration towards the surface of a composite at its HPHT sintering.